Contemporary meanings of planning and development. planning for integral territory development (2008)
In order to approach to the meaning of planning for integral development of the territory, the following thematic route is draws up: they are identified, in first instance, the main implications that from the context the global-premises, affect the contemporary time in the development processes, doing excellent the territorial perspective. They are exposed and they analyzed, in second instance, diverse essential and means of the planning that behaves at the same time as it bases conceptual. And, they recreate, in third instance, diverse approaches of the development, allowing to collect constituent senses of an integral notion.